Portal Hypertension and Myeloproliferative Neoplasms: A Relationship Revealed. (16th September 2013) - Toros, Ahmet Burak; Gokcay, Serkan; Cetin, Guven; Ar, Muhlis Cem; Karagoz, Yesim; Kesici, Besir
Abstract : Background/Objectives. Patients with myeloproliferative neoplasms have a well-established increased risk of thrombosis. Many trials report identification of an underlying myeloproliferative neoplasm by investigation of the patients developing portal hypertensive esophagus and/or fundus variceal hemorrhage in the absence of any known etiology. This trial was designed to investigate the association between myeloproliferative neoplasms and portal hypertension and to detect the frequency of portal hypertension development in this subset of patients. Methodology. Twenty-nine patients previously diagnosed with polycythemia vera, essential thrombocytopenia, and primary myelofibrosis, who were under followup at the hematology outpatient clinic of our hospital, were included in the trial. Results. In our trial, we detected portal hypertension in 13.8% of the patients (n = 4 ), as a finding that was similar to those obtained in other studies performed to date. Conclusions. Considering the fact that diagnosis of myeloproliferative neoplasms usually takes a long time, treatment should be started (while, on the other hand, assessing the investigational and therapeutical choices for the complications) right after the bone marrow biopsy or cytogenetic studies required for establishing the final diagnosis have been performed.